Hyperbolic-Parabolic Type Chemotaxis Systems in R^N (Journal of Partial Differential Equations, 2020)
In this paper, we discuss the local and global existence of weak solutions forsome hyperbolic-parabolic systems modeling chemotaxis in RN.
Keywords: Hyperbolic-parabolic system; KS model; chemotaxis.